STRATEGI IMPLEMENTASI MANAJEMEN MUTU BERBASIS TOTAL QUALITY MANAGEMENT DALAM PENGUATAN STANDAR KOMPETENSI LULUSAN PADA SMADI KABUPATEN BEKASI - Ayi Najmaul Hidayat; Zahra Zahra; Leli Nurleli; Aldi Putra Pangestu; Muhammad Herlingga (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation strategies of quality management based on Total Quality Management (TQM) in strengthening Graduate Competency Standards (GCS) at Senior High Schools. The study is motivated by the need to improve the quality of graduates who are not only academically competent but also possess strong character, 21st-century skills, and high competitiveness. A qualitative approach with a multi-case study design was employed. The research participants included school principals, teachers, school committee members, students, and other relevant stakeholders. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings indicate that the implementation of TQM-based quality management strategies is carried out through quality planning, quality program implementation, quality evaluation, and continuous improvement processes guided by the principles of continuous improvement and the PDCA (Plan-Do-Check-Act) cycle. The success of implementation is supported by school leadership, teacher competence, a strong quality culture, active participation of school committees, and support from parents and the community. These strategies contribute significantly to strengthening Graduate Competency Standards through improvements in students’ attitudes, knowledge, and skills. Furthermore, graduates demonstrate better adaptability, higher competitiveness, and greater readiness to pursue higher education and contribute positively to society. The study concludes that the systematic, participatory, and sustainable implementation of Total Quality Management-based quality management strategies effectively strengthens Graduate Competency Standards in Senior High Schools. Therefore, a strong commitment from all stakeholders is essential to foster a quality culture and improve educational outcomes, leading to the development of highly qualified and competitive graduates.